Polymer‐based microfluidic devices: A comprehensive review on preparation and applications. Issue 1 (3rd November 2021) - Han, Xue; Zhang, Yonghui; Tian, Jingkun; Wu, Tiange; Li, Zongwen; Xing, Fei; Fu, Shenggui
Abstract: As key components in life science, microfluidics devices play increasingly important roles in the fields of biomedicine, pharmaceuticals, and biology due to its high detection efficiency. Also, microfluidics devices have many applications in label‐free detection, thanks to their low cost and ease of operation. Traditionally, microfluidic devices are fabricated with glass and silicon materials. As an alternative, polymer materials are commonly used in the fabrication of microfluidic devices for their lower cost, versatile fabrication methods, biocompatibility, and repeatability. In this review, the methods for fabricating polymer microfluidic systems are described in detail, including lithography, hot embossing and imprinting, soft lithography, laser ablation, 3D printing, and other technologies. In particular, the merits and demerits of each of the methods are discussed comprehensively. This review also focuses on the applications of polymer‐based microfluidic systems in the areas of biology, medicine and production, typical application scenarios including blood, tumor cell and nucleic acid testing, oil adsorption detection, and pesticide detection. This review emphasizes the device preparation methods and application scenarios of polymer‐based microfluidic systems and was expected to arise more extensive discussions in this field. Abstract : This review summarizes diverse fabrication methods of microfluidics devices, including lithography, hot embossing and imprinting, soft lithography, laser ablation and 3D printing. Versatile applications based on polymer microfluidic systems in the areas of biology, medicine and production are reviewed as well.